PENGARUH PENGALAMAN KERJA, MOTIVASI KERJA DAN LATAR BELAKANG PENDIDIKAN TERHADAP KINERJA KARYAWAN (Studi Pada AJB Bumiputera Cabang Cibadak): Manajemen sumberdaya manusia - Raden Rijanto,SH., MM (P3M STIE PASIM Sukabumi, 2020)
The purpose of this study was to determine the effect of work experience on employee performance, the effect of work motivation on employee performance, the influence of education background on employee performance, the effect of work experience, work motivation and background on employee performance. The population is employees and agents of AJB Bumiputera, Cibadak Branch, with a sample of 56 employees and agents. The data collection technique used was a questionnaire. The analysis technique used is multiple regression analysis techniques. The results showed that work experience had a thitung of 3.759 with a ttable 2.006, which had a positive effect on performance. Work motivation on performance has a negative thitung of 2,217 with a ttable of 2,006, so it can be concluded that it does not have a contribution to performance. Education background (X3) on performance (Y). Variable X3 has a thitung of negative 2,337 with ttable 2,006, so thitung<ttable, so it can be concluded that variable X3 does not have a contribution to Y. This shows that the percentage contribution of the variable influence work experience, work motivation and education background on performance by 38,5%, while 61.5% is influenced or explained by other variables not examined.